Soil Quality Study Of Pomelo (Citrus Maxima (Burm) Merr) Plantation in Padanglampe Village, Pangkajene Regency - Asmita Ahmad; Andi Ravita Sari Musrini; Nurul Fajeriana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Pamelo orange plants represent a significant horticultural commodity with substantial economic value and are extensively cultivated in Pangkajene Regency. The quality of Pamelo fruit in Padanglampe Village varies, with some fruits being sweet and others slightly sour, suggesting that differing soil conditions may influence fruit quality. This study aims to investigate the soil quality of Pamelo plants in Padanglampe Village, Ma'rang District, Pangkajene Regency. A quantitative descriptive method was employed, involving the collection of secondary data, field surveys, primary data collection through soil sampling, and laboratory analysis of minimum data sets (pH, total nitrogen, available phosphorus, organic carbon, and exchangeable potassium). Soil quality indices were analyzed using statistical tests, including principal component analysis (PCA). The findings indicated that soil pH was slightly acidic, organic carbon content was low, and nitrogen, phosphorus, and potassium levels were categorized as medium. Correlation tests revealed a significant negative correlation at the 1% alpha level between bulk density and porosity, while organic carbon and soil pH were positively correlated at the 5% alpha level. The scree plot showed three eigenvalues corresponding to the main components in PCA1, PCA2, and PCA3 analyses, which can be further examined to determine the Soil Quality Index (SQI) value. The SQI-PC1 value of 0.55 was categorized as moderate, while the SQI-PC2 and SQI-PC3 values were classified as very low. However, the comprehensive soil quality index (CSQI) value was 0.97, indicating outstanding soil quality. This finding suggests that Padanglampe Village has highly favorable soil conditions for pomelo cultivation, though improved management practices are needed to sustain optimal production. The primary strength of this study lies in integrating chemical and physical soil indicators into a single comprehensive index, providing a more holistic assessment of land suitability for pomelo cultivation. Based on these findings, it is recommended that farmers prioritize areas with high SQI values as primary zones for pomelo development and implement sustainable soil management practices, particularly by increasing soil organic matter content and applying appropriate fertilizer management, to maintain soil quality and ensure the long-term sustainability of pomelo production.